Composition and conservation status of marine fish species traded in the traditional markets of Pangandinang City - Baifa, Baifa; Pratiwi, Fika Dewi; Farhaby, Arthur Muhammad (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2024)
Traditional markets are places where people buy and sell basic necessities, including sea fish. Marine fish include fisheries resources that have important economic value which are identified based on their classification, namely pelagic fish and demersal fish. Identification of fish at species level is important for determining conservation status and composition of fish species. This research aims to analyze the composition of fish species and the conservation status of marine fish species traded in the traditional markets of Pangkalpinang City. This research was carried out in October 2023 in four traditional markets in Pangkalpinang City. The research method uses a survey method with interviews with traders and observations in four traditional markets in Pangkalpinang City. The types of marine fish traded in the 4 Traditional Markets of Pangkalpinang City were identified as 30 families and 55 species of marine fish consisting of small pelagic, large pelagic and demersal fish. The composition of marine fish species obtained at the 4 Traditional Markets of Pangkalpinang City was 5286 individual fish. 1296 individual fish at Ratu Tunggal Market, Kranas Block, 1927 individual fish at Pangkalpinang Morning Market, 1035 individuals at Rumput Market, and 1028 individual fish at Parit Lalang Market. Based on search results on the IUCN website, there are six criteria for the conservation status of marine fish species traded in Pangkalpinang City traditional markets, namely 45 fish species classified as Least Concern (LC), 3 species classified as Near Threatened (NT), 3 species classified as Data Deficient (DD), 3 species are classified as Vulnerable (VU) and 1 species is classified as Critically Endangered (CR). Meanwhile, according to CITES data, there is one species that is classified as Appendix II and based on the national status, the types of marine fish in traditional markets are not protected or there are no national regulations or are not included in KEPMEN KP Number 1 of 2021.